SYT1-Associated Neurodevelopmental Disorder: A Narrative Review - Edith Riggs; Zaynab Shakkour; Christopher L. Anderson; Paul R. Carney (MDPI AG, 2022)
Synaptic dysregulations often result in damaging effects on the central nervous system, resulting in a wide range of brain and neurodevelopment disorders that are caused by mutations disrupting synaptic proteins. SYT1, an identified synaptotagmin protein, plays an essential role in mediating the release of calcium-triggered neurotransmitters (NT) involved in regular synaptic vesicle exocytosis. Considering the significant role of SYT1 in the physiology of synaptic neurotransmission, dysfunction and degeneration of this protein can result in a severe neurological impairment. Genetic variants lead to a newly discovered rare disorder, known as SYT1-associated neurodevelopment disorder. In this review, we will discuss in depth the function of SYT1 in synapse and the underlying molecular mechanisms. We will highlight the genetic basis of SYT1-associated neurodevelopmental disorder along with known phenotypes, with possible interventions and direction of research.